2020
DOI: 10.3390/insects11120840
|View full text |Cite
|
Sign up to set email alerts
|

Similar Gut Bacterial Microbiota in Two Fruit-Feeding Moth Pests Collected from Different Host Species and Locations

Abstract: Numerous gut microbes are associated with insects, but their composition remains largely unknown for many insect groups, along with factors influencing their composition. Here, we compared gut bacterial microbiota of two co-occurring agricultural pests, the peach fruit moth (PFM), Carposina sasakii, and the oriental fruit moth (OFM), Grapholita molesta, collected from different orchards and host plant species. Gut microbiota of both species was mainly composed of bacteria from Proteobacteria, followed by Firmi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…At the phylum level, there were no significant differences in the bacterial composition of G. molesta across the five diets of apples, peaches, nectarines, crisp pears, and peach shoots, but the diversity of gut bacteria was significantly lower than that of the artificial feed and plums. In these five treatments, Proteobacteria was the absolute dominant phylum, and its relative abundances were more than 90%, similar to previous researches [20,31,33]. However, in the two treatment groups that fed on an artificial feed and plums, the following four phyla were dominant: Proteobacteria, Firmicutes, Bacteroidota, and Actinobacteriota.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…At the phylum level, there were no significant differences in the bacterial composition of G. molesta across the five diets of apples, peaches, nectarines, crisp pears, and peach shoots, but the diversity of gut bacteria was significantly lower than that of the artificial feed and plums. In these five treatments, Proteobacteria was the absolute dominant phylum, and its relative abundances were more than 90%, similar to previous researches [20,31,33]. However, in the two treatment groups that fed on an artificial feed and plums, the following four phyla were dominant: Proteobacteria, Firmicutes, Bacteroidota, and Actinobacteriota.…”
Section: Discussionsupporting
confidence: 87%
“…The larvae were selected and surface-sterilized in 75% ethanol for 60 s, followed by 3 washes in sterile water for 30 s. Midgut tissues were dissected with sterile forceps in a sterile petri dish with a diameter of 90 mm and rinsed again in sterile phosphate buffered saline (PBS) [7,20,31,33]. Fifty midguts were collected per sample using a sterile centrifuge tube.…”
Section: Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taxonomic analysis revealed that the wild ghost moth gut bacterial community was dominated by Proteobacteria and Firmicutes (>99%), while the laboratory-reared ghost moth gut bacterial community was mainly composed of Proteobacteria with significantly decreased abundance in Firmicutes, but increased abundance in Bacteroidetes and Actinobacteria ( Figure 1 ). These four phyla were also the most common found in other lepidopteran species [ 35 , 52 , 53 , 54 ]. In this study, the fungal community of the ghost moth populations primarily consisted of Ascomycota and Basidiomycota , which was similar to other lepidopteran insects [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that amplicon sequencing targeting the 16S rRNA V3–V4 regions, which is commonly used to examine the diversity of bacteria in a particular niche, may assign the genus Acetobacter to bacteria taxonomically closer to G55GP T . The genus Acetobacter is often identified by V3–V4 amplicon sequencing in insect guts, including beetles [41], fruit flies [42] and moths [43]. Although some fruit flies do actually harbour Acetobacter [44], it may well be that other insects carry bacteria more closely related to G55GP T .…”
Section: Genome Featuresmentioning
confidence: 99%